Estudo de validação de espécies da flora maranhense na terapêutica do câncer: contribuição para obtenção de bioprodutos e promoção da farmacovigilância - GODINHO, Jéssyca Wan Lume da Silva (2023)
Cancer is a multifactorial disease, constituting a serious global public health problem. In the search for new anticancer agents, natural resources, especially of plant origin, represent an important source, since several drugs made available in the current therapy were obtained from plant species; this should stimulate research, requiring efforts and resources in the development of validation studies, especially of popularly used species. In this sense, the ethnopharmacological approach represents an important tool for the selection of plant species for these studies. Thus, this work aims to develop a validation study of local flora species popularly used in cancer treatment by the population of São Luis/Maranhão; contributing to the D&R of new therapeutic options in cancer treatment. The research started from a bibliographic survey in databases of probable plant species with anticancer potential according to ethnopharmacological studies published from 2001 to 2020. Next, field research was conducted, with an ethnopharmacological approach, and 227 patients from health facilities specialized in cancer treatment in São Luís, Maranhão, from June to December 2019 were interviewed. Based on ethnopharmacological data, a plant species with anticancer potential is popularly reported for chemical and cytotoxicity studies. In the bibliographic survey, the species Zingiber officinale Roscoe (ginger), Allium sativum L. (garlic), Allium cepa L. (onion), Aloe vera (L.) Burm. f. (aloe), and Annona muricata L. (soursop); these species have several studies that prove antitumor activity, but without guarantee of safety due to the scarcity of clinical data (Chapter 1). In the ethnopharmacological study conducted, the five most cited species were Annona muricata L. (soursop), Kalanchoe daigremontiana (Raym.-Hamet & Perrier) A.Berger (arantho), Senna alexandrina Mill. (senna), Morinda citrifolia L. (none) and Dysphania ambrosioides L. Mosyakin & Clemants (epazote) (Chapter 2). Chemical studies and antioxidant and cytotoxic activities were carried out with extract from Kalanchoe daigremontiana leaves obtained by maceration with ultrasound (hydromodule 1:6), with chemical identification performed by high-efficiency liquid chromatography coupled to mass spectrometry with electrospray ionization; and the evaluation of antioxidant and cytotoxic activities made in vitro by photocolorimetry and human cancer cell lines (HeLa) and non-tumor human fibroblast cells (GM 0492A), respectively. The results showed the presence of galloylquinic acid and two compounds derived from kaempferol in arantho extract, antioxidant activity with CE50 6.71 μg/mL, and cytotoxic activity with IC50 values for tumor cells of 21.95 μg/mL and for normal cells of 93.25 μg/mL. (Chapter 3). These data together encourage the continuity of the validation of the antitumor activity of the species by complementary in vitro and in vivo assays in view of the antineoplastic potential found here and reinforce the role of ethnopharmacology as a tool, both in the selection of plant species for Research and Development of new bioproducts, as well as in the identification of risks and dangers associated with the popular therapeutic use of plants without efficacy and encouraging pharmacovigilance actions in Phytotherapy.